2018
DOI: 10.1002/jctb.5606
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic analysis of the influence of iron‐oxidizing bacteria on antimony (V) removal from water by microscale zero‐valent iron

Abstract: BACKGROUND Microscale zero‐valent iron (mZVI) is an efficient material for removing heavy metals from water, and iron‐oxidizing bacteria are the primary microorganisms responsible for iron corrosion. We investigated the effects of Sphaerotilus natans on antimony [Sb(V)] removal by mZVI using batch experiments. RESULTS At an initial Fe0 dose of 0.1 g L–1, 40 mg L–1 Sb(V) was almost completely removed in an abiotic system. Although S. natans exhibited significant tolerance to Sb(V), its ability to adsorb Sb(V) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Based on the leaching results, it could be confirmed that MBT had the better curing performance of Sb. The higher UCS of MBT was attributed to the formation of more hydration products, which yielded a denser structure and thus reduced the release of Sb from tailings [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the leaching results, it could be confirmed that MBT had the better curing performance of Sb. The higher UCS of MBT was attributed to the formation of more hydration products, which yielded a denser structure and thus reduced the release of Sb from tailings [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Fourier‐transform infrared spectra of S. montanus , S. natans and T. fructosivorans are shown in Figure 1. In the spectra, the broad bands around 3422 and 3302 cm −1 are assigned to the stretching modes of N‐H of amides and ‐OH bonds, (Li, Wu, et al, 2018; Li, Zhu, et al, 2018; Loukidou et al, 2003; Pagnanelli et al, 2004). The broad band around 3068 cm −1 is assigned to the =C‐H stretching vibration (Busca et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…It is an oxyanion and the nature of adsorption sites is completely different from those found in cation adsorptions. Although high capacities have often been obtained when using anion exchange resins (Chen et al, 2019; Lee et al, 2005; Li, Wu, et al, 2018; Li, Zhu, et al, 2018; Nebeker & Hiskey, 2012) and other synthetic adsorbents, (Drout et al, 2018; Han et al, 2018; Li et al, 2020; Rajec et al, 2015) it is difficult to reduce the cost of preparation of these materials, compared with chars or minerals. (Hu et al, 2015; Huang & Hu, 2020; Mulcahy et al, 1990; Wakoff & Nagy, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, the oxidation behavior and mechanism of Sb(III) under coupling-mediated iron/manganese (hydr)oxides between microbes has not yet been described in literature. Therefore, the oxidation behavior of Sb-oxidizing bacteria induced by iron and manganese oxide is also a future research priority ( Nguyen et al, 2017a , b ; Li Y. et al, 2018 ).…”
Section: The Performance and Molecular Mechanism Of Sb-oxidizing Bacteriamentioning
confidence: 99%